O problema da relação mente-corpo e a consciência como sua manifestação - Faria, Daniel Luporini de [UNESP] (2006)
This dissertation analyses the mind-body relation in its ontological and epistemological perspectives. It's main focus of analysis is the treatment of questions associated to equivalent notions of sensation, consciousness, conscientious experience, or simply experience. Thus, starting with the supposition that the mind-body relation is a philosophical problem, mainly in the context of the Cartesian philosophy, it is investigated the way such a problem is treated under the materialist and functionalist perspectives in the philosophy of mind. The materialist approach investigated is based on the mind-brain identity theory proposed by Smart's (1970), and on versions of eliminativism formulated by Churchland (2004). In relation to the functionalist approach, it is investigated the possibility of defining functionally the qualitative aspects of experience, specially from the perspective delineated by Shoemaker (1980). A certain scepticism is indicated concerning the materialist and the functionalist perspectives investigated, it is argued that strictly speaking, they fail in their attempts to solve the mind-body problem and to explain conscientious experiences. However, in order to avoid scepticism in relation to these problems, it is suggested that the mind-body problem and the epistemological nature of conscientious experience can be better understood Ryle relational perspective. According to this perspective, the mind is conceived not as a thing (res), situated in a recipient with privileged introspective access, but as a disposicional property of the multiple vias expressed in behaviour and in the lived history of each system.